2021
DOI: 10.1080/09658211.2021.1912101
|View full text |Cite
|
Sign up to set email alerts
|

Adults’ perceptions of forgetful children: the impact of child age, domain, and memory type

Abstract: Prospective memory (PM) tasks have been described as social in nature because carrying out one's intentions often has an impact on others. Despite the claim that PM errors (compared to retrospective memory [RM] errors) are perceived as character flaws, little empirical work has tested this assertion. In particular, no study has examined how adults perceive children's PM errors. Thus, the aim of the current studies was to examine adults' perceptions of children's forgetfulness depending on child age (4 vs. 10-y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…On the one hand, this finding could confirm Munsat's claim (1965), according to which people with bad PM would be negatively perceived by others, might also occur in school. Similarly, a recent study showed that adults tend to judge children, especially older children, with bad PM as having a flawed personality (Moeller et al, 2021). On the other hand, the influence of PM over grades could have been mediated by other cognitive skills, which may contribute to both PM and academic performance.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…On the one hand, this finding could confirm Munsat's claim (1965), according to which people with bad PM would be negatively perceived by others, might also occur in school. Similarly, a recent study showed that adults tend to judge children, especially older children, with bad PM as having a flawed personality (Moeller et al, 2021). On the other hand, the influence of PM over grades could have been mediated by other cognitive skills, which may contribute to both PM and academic performance.…”
Section: Discussionmentioning
confidence: 96%
“…Contrary to the hypotheses, teachers' evaluations of children's social skills were not affected by their PM performance. Based on Munsat ( 1965 ) and on the recently published study by Moeller et al ( 2021 ), it was expected that children with low PM performance would also be evaluated as being less socially skilled than participants with higher PM ability. However, our model did not reveal a significant relation between PM performance and social skills evaluations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, PM develops considerably during childhood, typically reaching its peak only in late adolescence or young adulthood (Zimmermann & Meier, 2006). Considering the negative consequences that frequent forgetting of intentions can have on children's academic success, social relationships, health, and well-being (e.g., Basso et al, 2023;Moeller et al, 2021), researchers have recognized the necessity to investigate ways to support children's PM performance (see Cottini, 2023, for a review of the literature). For instance, recent studies have shown that prompting children to imagine performing the PM task beforehand, namely, giving episodic future thinking (EFT) instructions or asking them to predict their PM performance (i.e., metacognitive monitoring), can improve children's PM performance (Cottini et al, 2018;Kretschmer-Trendowicz et al, 2016.…”
Section: Backgrou N Dmentioning
confidence: 99%
“…The ability to remember and execute intended actions, defined as prospective memory (PM; Einstein & McDaniel, 1990 ), does not fully develop until late adolescence or young adulthood and children often rely on adults’ support (Kretschmer-Trendowicz & Altgassen, 2016 ; Zimmermann & Meier, 2006 ). Notwithstanding, at the start of primary school, children are gradually expected to remember intentions independently (Hajdas et al, 2021 ) and are often judged negatively by adults when they fail to do so (Moeller et al, 2021 ). School-aged children who frequently fail to remember are likely to be disadvantaged in various contexts of their life: in school, when they forget to do their homework or to complete assignments; in their relationships, when they forget to return a toy to a friend or to convey messages to their parents, and regarding their health and well-being, when they forget to wear a helmet when bike riding or to take the lunchbox to school (Mahy et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%